Analisis Pengaruh Modal Inti terhadap Profitabilitas dengan Mediasi Dana Pihak Ketiga Dan Kredit yang Diberikan pada Bank Perkreditan Rakyat di Indonesia Periode 2015-2023 - Nindi Anggi Wardan; Sri Wahyuning; Eka Satria Wibawa; Dhevi Dadi Kusumaningtyas (Jurnal Ilmiah Ekonomi, Akuntansi, dan Pajak, 2024)
This study on profitability aims to analyze the effect of Core Capital on Profitability with the mediation of Third Party Funds and Credit Given at Rural Credit Banks in Indonesia for the period 2015-2023. The sample used in this study was 108 monthly data, selected using the purposive sampling method. The monthly data comes from the Indonesian Banking Statistics report published by the Financial Services Authority (OJK). The data analysis technique used is path analysis using multiple linear regression. The results of the study indicate that Core Capital has a significant positive effect on Third Party Funds, Core Capital does not affect Credit Given, Third Party Funds have a significant positive effect on Credit Given, Core Capital and Party Funds do not have a significant effect on Profitability, Credit Given does not have a significant effect on Profitability, Third Party Funds and Credit Given are unable to mediate the effect of Core Capital on Profitability and Credit Given is unable to mediate the effect of Third Party Funds on Profitability.